The anatomy and palaeobiology of the early armoured dinosaur Scutellosaurus lawleri (Ornithischia: Thyreophora) from the Kayenta Formation (Lower Jurassic) of Arizona. Issue 7 (21st July 2021) - Breeden, Benjamin T.; Raven, Thomas J.; Butler, Richard J.; Rowe, Timothy B.; Maidment, Susannah C. R.
Abstract : The armoured dinosaurs, Thyreophora, were a diverse clade of ornithischians known from the Early Jurassic to the end of the Cretaceous. During the Middle and Late Jurassic, the thyreophorans radiated to evolve large body size, quadrupedality, and complex chewing mechanisms, and members of the group include some of the most iconic dinosaurs, including the plated Stegosaurus and the club-tailed Ankylosaurus ; however, the early stages of thyreophoran evolution are poorly understood due to a paucity of relatively complete remains from early diverging thyreophoran taxa. Scutellosaurus lawleri is generally reconstructed as the earliest-diverging thyreophoran and is known from over 70 specimens from the Lower Jurassic Kayenta Formation of Arizona, USA. Whereas Scutellosaurus lawleri is pivotal to our understanding of character-state changes at the base of Thyreophora that can shed light on the early evolution of the armoured dinosaurs, the taxon has received limited study. Herein, we provide a detailed account of the osteology of Scutellosaurus lawleri, figuring many elements for the first time. Scutellosaurus lawleri was the only definitive bipedal thyreophoran. Histological studies indicate that it grew slowly throughout its life, possessing lamellar-zonal tissue that was a consequence neither of its small size nor phylogenetic position, but may instead be autapomorphic, and supporting other studies that suggest thyreophorans had lower basal metabolic rates than other ornithischian dinosaurs. Faunal diversity of the Kayenta Formation in comparison with other well-known Early Jurassic-aged dinosaur-bearing formations indicates that there was considerable spatial and/or environmental variation in Early Jurassic dinosaur faunas.